2001
DOI: 10.1046/j.1523-1755.2001.0590041466.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial nitric oxide synthase inhibitory factor in some patients with chronic renal disease

Abstract: High plasma levels of ADMA in CRD patients are independent of reduced renal clearance, suggesting an alteration in ADMA synthesis and/or degradation. High ADMA is a marker and is partly responsible for the inhibition of eNOS activity in cultured cells and may also result in reduced eNOS activity in vivo, with consequent hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 29 publications
(32 reference statements)
3
34
1
Order By: Relevance
“…In a small series (n = 11) we found that plasma ADMA levels are variable in CKD patients and are not correlated with severity of CKD. 94 Similar findings have been reported by Saran and colleagues. 90 By contrast, Fleck et al reported mild but consistent elevation of plasma ADMA levels (30-40% higher than normal) in CKD patients, which did not correlate with concentrations of plasma creatinine.…”
Section: Adma In Chronic Kidney Diseasesupporting
confidence: 85%
See 2 more Smart Citations
“…In a small series (n = 11) we found that plasma ADMA levels are variable in CKD patients and are not correlated with severity of CKD. 94 Similar findings have been reported by Saran and colleagues. 90 By contrast, Fleck et al reported mild but consistent elevation of plasma ADMA levels (30-40% higher than normal) in CKD patients, which did not correlate with concentrations of plasma creatinine.…”
Section: Adma In Chronic Kidney Diseasesupporting
confidence: 85%
“…In a small group of patients (n = 11) with various primary diseases and approximately 30% residual renal function, an inhibitor of endothelial NOS was detected in the plasma of only 5 patients. 94 As shown in Figure 5, plasma ADMA levels in the CKD patients were predictive of endothelial NOS activity. ADMA concentrations were not correlated with primary disease or medication.…”
Section: Adma In End-stage Renal Diseasementioning
confidence: 88%
See 1 more Smart Citation
“…Indeed, in several subsequent studies, significantly increased plasma ADMA levels have been documented in patients with terminal renal failure (27)(28)(29). It has also been shown that these ADMA concentrations are sufficiently high to reduce significantly NO production ex vivo (30). The results of Zoccali et al (29) in a prospective study that comprised 225 patients with terminal renal failure are also in line with an important pathophysiologic role of ADMA in (cardio)vascular dysfunction.…”
Section: Discussionmentioning
confidence: 84%
“…methylated L -arginine derivatives and guanidino compounds), which can potentially depress NO synthase activity. Such compounds are thought to increase in the plasma more or less in proportion to the increase in the serum creatinine [22,23]. Furthermore, renal impairment is associated with oxidative stress which promotes NO inactivation by the production of reactive oxygen species, which avidly react with NO, producing cytotoxic reactive nitrogen species capable of nitrating proteins and damaging other molecules [24].…”
Section: Introductionmentioning
confidence: 99%